Faktor Kualitas Audit, Beban Kerja, Dan Pengalaman Auditor Dalam Menilai Kasus Kecurangan Di Kantor Akuntan Publik Leonard, Mulia, Dan Richard Cab. Semarang - David Karuna Dananjaya; Arief Himmawan Dwi Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to determine the effect of Audit Quality, Workload and Auditor Experience in Assessing Fraud Cases at the Public Accounting Firm Leonard, Mulia, and Richard Cab. Semarang. This study used a quantitative approach using primary data, namely data sourced from the results of questionnaires of 50 respondents. Data collection techniques use full sampling techniques. The data analysis methods used are data quality test, classical assumption test, multiple linear regression analysis, model test, and hypothesis test. Data is processed using SPSS software. The results of this study showed that (1) the variable Audit Quality has a positive and significant effect on assessing fraud cases, (2) The Workload variable has no effect and is not significant in assessing fraud cases, and (3) The Auditor Experience variable has a positive and significant effect in assessing fraud cases.